Optimization design and thinking of new knowledge of primary school mathematics under the perspective of high-order thinking cultivation: Take the surface area of the cylinder as an example - Zhang, Simin; Jie, Qin; Pereira, Jerito (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2023)
The 20th report clearly emphasizes the importance of training innovative talents, and the cultivation of higher-order thinking has been paid attention to. Micro-lesson is a new teaching method to cultivate and develop students' high-level thinking. Taking cylindrical surface micro-lesson design as an example, this paper, starting from practice, compares the micro-lesson design and fragment record before and after optimization, and puts forward suggestions for optimization design: Pay attention to the construction of knowledge system and develop general thinking; Pay attention to summary reflection, form critical thinking; Pay attention to situation creation and develop innovative thinking; Focus on problem chain design and develop logical thinking. In order to provide reference for primary school mathematics classroom micro-lesson design. In order to provide reference for primary school mathematics classroom micro- lesson design.